Collaborative innovation in Food SMEs: a practice approach - Caridà, Angela; Colurcio, Maria (Archives of Business Research, 2014)
The work focuses on the collaborative innovation. It emphasizes the role of relationship and of the resource integration process for the development on innovation and aims to define a practice to support management in the development and fostering of networked innovation process in SMEs. This paper addresses the topic of collaborative innovation in the food SMEs by presenting the results of two studies. The study 1 concerns empirical evidences from 155 Italian food SMEs. It describes the state of the art of the innovation in the Italian food SMEs context. The study 2 relates an in-depth analysis of 10 Italian food SMEs. It frames the innovative behaviour of the firms investigated according to the practice theory.